Selective On-Surface Metalation and Uncommon Reordering of Self-Assembled Macrocyclic Biquinazoline Ligands on Ag(111) - Haag, Felix; Zhao, Wenchao; Yang, Biao; Knecht, Peter; Seufert, Knud; Cuxart, Marc G.; Papageorgiou, Anthoula C.; Muntwiler, Matthias; Auwärter, Willi; Hess, Corinna R.; Barth, Johannes V.; Allegretti, Francesco (Chemistry – A European Journal, 2025)
The macrocyclic biquinazoline ligand, H-Mabiq, presents a central and a peripheral site for the coordination of metal ions, making the adsorption on solid surfaces promising for the creation of self-assembled bimetallic two-dimensional platforms. Here, we apply an on-surface metalation strategy under ultra-high vacuum conditions to guide the synthesis of metalated species and study sequential metalation patterns. We find that cobalt (as well as iron) metalation on the Ag(111) surface preferentially occurs at the macrocyclic centre without further metal coordination to the peripheral site. Nevertheless, starting from a densely packed, self-assembled H-Mabiq monolayer, the modification of the central cavity by Co is accompanied by an unusual, metalation-induced phase transformation which gives evidence of modified lateral / interfacial interactions. The selective metalation of one molecular site opens up an on-surface route to create bimetallic networks incorporating select metal ions at different locations.
Keywords: Macrocyclic complexesIn-situ MetallationOn-surface self-assemblyPhotoelectron spectroscopyScanning tunnelling microscopy